A catalytic oxidation catalyst, a method for preparing the same, and an application thereof

CN118179534BActive Publication Date: 2026-10-09CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211575684.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-09
Publication Date
2026-10-09
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

而对于活性更高的Cu、Co、Ni、Mo系催化剂,因其高成本和存在二次污染问题影响其工业应用,因此开发一种具有高催化活性的同时能够降低金属溶出的催化剂是目前本领域重点研发方向

Benefits of technology

1、本发明提供的催化氧化催化剂具有双活性组分,其中硫化亚铁不但具有催化氧化剂生成高活性自由基的作用,还能起到助催化作用,与过渡金属氧化物协同进行催化氧化,提高对污染物的去除效果。在催化剂的具体应用反应过程中包括两级催化反应,氧化剂和污染物分子首先与外层的硫化亚铁反应消耗掉一部分;穿过孔道与氧化铜接触的氧化剂和有机污染物浓度均已经降低,此时与具有更高活化能力的氧化铜进行催化反应进行深度处理降解污染物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118179534B_ABST
    Figure CN118179534B_ABST
Patent Text Reader

Abstract

The application discloses a catalytic oxidation catalyst and a preparation method and application thereof. The catalyst is a core-shell structure, wherein the inner core is activated carbon loaded with copper oxide and optional ferrous sulfide, and the shell is silicon oxide loaded with nano ferrous sulfide. The preparation method comprises the following steps: mixing activated carbon particles with a soluble copper salt solution, drying and roasting to obtain material A; adding the material A into a polyvinyl alcohol solution, drying to obtain material B; preparing material C; mixing the material B with the material C to react, then washing, drying and roasting to obtain material D; uniformly mixing ferrous sulfate solution, a stabilizer and the material D to obtain material E; uniformly mixing a sulfur compound, a surfactant and water under the protection of an inert atmosphere, then slowly adding the mixture into the material E, adjusting the pH value of the system to react, drying and roasting to obtain the catalyst product. The application further provides a wastewater treatment method using the catalytic oxidation catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, and in particular relates to a catalytic oxidation catalyst and its preparation method. Background Technology

[0002] Because recalcitrant organic pollutants are difficult to degrade using conventional methods, researchers have developed advanced oxidation technologies (AOPs) that utilize free radicals with high oxidation potentials and strong oxidizing properties, activated by oxidants such as hydrogen peroxide, percarbonate, ozone, and persulfate, to efficiently oxidize and degrade organic pollutants. AOPs offer advantages such as rapid reaction rates, strong oxidizing power, near-non-selectivity for organic matter, and high mineralization rates, attracting increasing attention.

[0003] Activation of oxidants typically requires the action of a catalyst. Currently, commonly used advanced oxidation catalysts generally use transition metals as active components. Iron and iron-containing compounds are often used as activating materials for advanced oxidation reactions due to their low cost and environmental friendliness. However, the industrial application of Cu, Co, Ni, and Mo catalysts, which have higher activity, is limited by their high cost and secondary pollution problems. Therefore, developing a catalyst with high catalytic activity while reducing metal dissolution is a key research direction in this field.

[0004] CN202210083673.2 discloses a method for preparing modified attapulgite loaded with ferrous sulfide and its application, belonging to the field of environmental functional composite materials technology. The preparation method of this invention includes the following steps: first, attapulgite is heated in a muffle furnace; then, the thermally activated attapulgite is immersed in dilute acid, shaken and mixed, then centrifuged, washed, and dried to obtain thermally acid-modified attapulgite; subsequently, under nitrogen protection, an aqueous solution of ferrous chloride is added to the above modified attapulgite, stirred evenly, and then an aqueous solution of sodium sulfide is added dropwise for reaction. After the reaction is complete, the mixture is allowed to stand and separate into layers, rinsed, and dried to obtain modified attapulgite loaded with ferrous sulfide. This invention can be used for the removal of molybdate in water and has good market application prospects.

[0005] CN201911178706.6 discloses a magnetic carbon-supported nano-ferrous sulfide Fenton catalyst and its preparation method. The catalyst consists of ferrous sulfide and magnetite supported on biochar, with a mass ratio of ferrous sulfide to magnetite of 1:1 to 1.5:1 and a mass ratio of ferrous sulfide to biochar of 1:3 to 1:5. The Fenton-like catalyst obtained according to the preparation method of this invention exhibits good magnetic properties and higher reactivity in catalyzing Fenton-like reactions, showing significant effects in the Fenton-like oxidation and degradation of organic wastewater containing antibiotics, dyes, etc. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the main objective of this invention is to provide a catalytic oxidation catalyst, its preparation method, and its application. The catalyst is characterized by its high catalytic degradation ability for organic pollutants.

[0007] The first aspect of the present invention provides a catalytic oxidation catalyst, the catalyst having a core-shell structure, wherein the core is activated carbon supported on copper oxide and optionally ferrous sulfide, and the outer shell is silicon oxide supported on nano-ferrous sulfide.

[0008] Furthermore, according to a specific embodiment of the present invention, the catalytic oxidation catalyst includes two levels of channels, wherein the size of the first level channel is less than 2 nm and the size of the second level channel is 2 to 20 nm; further still, the pore volume of the first level channel accounts for 60 to 90% of the total pore volume, and the pore volume of the second level channel accounts for 10 to 40% of the total pore volume.

[0009] Furthermore, according to a specific embodiment of the present invention, the specific surface area of ​​the catalytic oxidation catalyst is 200–1200 m². 2 / g.

[0010] Furthermore, according to a specific embodiment of the present invention, based on the weight of the catalytic oxidation catalyst, the core weight is 70-90% of the catalyst weight, and the outer shell weight is 10-30% of the catalyst weight.

[0011] Furthermore, according to a specific embodiment of the present invention, based on the weight of the catalytic oxidation catalyst, the weight of ferrous sulfide accounts for 5 to 20% of the weight of the catalyst.

[0012] Furthermore, according to a specific embodiment of the present invention, based on the weight of the catalytic oxidation catalyst, the weight of copper oxide accounts for 2 to 10% of the weight of the catalyst.

[0013] Furthermore, according to a specific embodiment of the present invention, the molar ratio of iron to copper in the catalytic oxidation catalyst is greater than 1.2:1.

[0014] A second aspect of the present invention provides a method for preparing a catalytic oxidation catalyst, comprising the following steps: Step 1: Mix activated carbon granules with a soluble copper salt solution, and after mixing, dry and calcine under anaerobic conditions to obtain material A; Step 2: Add material A to a polyvinyl alcohol solution for treatment, and then further dry to obtain material B; Step 3: Mix the silicon source, additives, silica-alumina clay, binder, alcohol and water evenly to obtain material C; Step 4: Mix material B and material C to react, and then wash, dry and calcine to obtain material D; Step 5: Dissolve ferrous sulfate in deoxygenated water, then add stabilizer and mix evenly under an inert atmosphere. Then add material D and mix well to obtain material E. Step 6: Under an inert atmosphere, the sulfur-containing compound, surfactant, and water are mixed evenly and then slowly added to material E. The pH of the system is adjusted to 6-8, and the temperature is raised to 60-80℃ for reaction. After drying and calcination, the catalyst product is obtained.

[0015] Furthermore, according to a specific embodiment of the present invention, the activated carbon particles mentioned in step one are shaped activated carbon particles, and the shape of the activated carbon particles can be any one of irregular particles, cylindrical, spherical, clover, four-leaf clover, or toothed sphere.

[0016] Furthermore, according to a specific embodiment of the present invention, in the activated carbon particles described in step one, pores smaller than 2 nm account for more than 90% of the total pores.

[0017] Furthermore, according to a specific embodiment of the present invention, the soluble copper salt mentioned in step one is one or more of copper sulfate, copper nitrate, copper chloride, and copper acetate, preferably copper nitrate.

[0018] Furthermore, according to a specific embodiment of the present invention, the drying temperature in step one is 60-110°C and the drying time is 2-12 hours; preferably, the drying temperature is 70-90°C and the drying time is 3-5 hours.

[0019] Furthermore, according to a specific embodiment of the present invention, in step one, the calcination temperature under anaerobic conditions is 400-800°C, and the calcination time is 2-8 hours; preferably, the calcination temperature is 500-700°C, and the calcination time is 3-4 hours.

[0020] Furthermore, according to a specific embodiment of the present invention, the mass concentration of the polyvinyl alcohol solution in step two is 0.1-2.0%, and the polyvinyl alcohol solution is generally obtained by dissolving polyvinyl alcohol in water at 55-95°C.

[0021] Furthermore, according to a specific embodiment of the present invention, the processing in step two is a mixed processing, preferably carried out under ultrasonic conditions, with the ultrasonic conditions being 40 kHz and the processing time being 0.2 to 2 hours.

[0022] Furthermore, according to a specific embodiment of the present invention, in step two, the volume of the polyvinyl alcohol solution is 0.7 to 1.0 times the volume of water absorbed by the activated carbon.

[0023] Furthermore, according to a specific embodiment of the present invention, the drying temperature in step two is 50-100°C and the drying time is 3-8 hours; preferably, the drying temperature is 70-80°C and the drying time is 4-6 hours.

[0024] Furthermore, according to a specific embodiment of the present invention, the silicon source in step three is methyl orthosilicate and / or ethyl orthosilicate, preferably ethyl orthosilicate.

[0025] Furthermore, according to a specific embodiment of the present invention, the auxiliary agent in step three is at least one of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, and octadecyltrimethylammonium bromide.

[0026] Furthermore, according to a specific embodiment of the present invention, the silica-alumina clay in step three is nanoparticles with a diameter of 2 to 5 nm, wherein the sum of the contents of silicon oxide and aluminum oxide accounts for more than 65% of the total mass of the silica-alumina clay.

[0027] Furthermore, according to a specific embodiment of the present invention, the alcohol in step three is a small molecule alcohol, specifically methanol and / or ethanol, preferably ethanol.

[0028] Furthermore, according to a specific embodiment of the present invention, the binder in step three is at least one of methylcellulose, ethylcellulose, carboxymethylcellulose, and hydroxypropylmethylcellulose.

[0029] Furthermore, according to a specific embodiment of the present invention, the mass ratio of the amount of silica-alumina clay to the amount of silicon source in step three is less than or equal to 1:6.

[0030] Furthermore, according to a specific embodiment of the present invention, the washing in step four is washing with water, specifically washing with water at 70-90°C several times, specifically 1-4 times.

[0031] Furthermore, according to a specific embodiment of the present invention, the drying temperature in step four is 60-110°C and the drying time is 2-12 hours; preferably, the drying temperature is 70-90°C and the drying time is 3-5 hours.

[0032] Furthermore, according to a specific embodiment of the present invention, the calcination in step four is carried out under anaerobic conditions, with a calcination temperature of 400–800°C and a calcination time of 2–8 hours; preferably, the calcination temperature is 500–700°C and the calcination time is 3–4 hours.

[0033] Furthermore, according to a specific embodiment of the present invention, the stabilizer in step five is at least one of starch and cellulose, wherein the starch can be at least one of sweet potato starch, corn starch, and potato starch; and the cellulose can be at least one of methylcellulose, ethylcellulose, carboxymethylcellulose, and hydroxypropylmethylcellulose.

[0034] Furthermore, according to a specific embodiment of the present invention, the sulfur-containing compound in step six is ​​selected from at least one of sodium sulfide and thioacetamide (CH3CSNH2).

[0035] Furthermore, according to a specific embodiment of the present invention, the surfactant in step six is ​​at least one of the Span series surfactants and the Tween series surfactants. Specifically, the Span series surfactant is at least one of Span 20, Span 40, Span 60, and Span 80; the Tween series surfactant can be at least one of Tween 20, Tween 40, Tween 60, and Tween 80.

[0036] Furthermore, according to a specific embodiment of the present invention, the drying in step six is ​​carried out under anaerobic conditions, preferably by rotary evaporation drying, with a drying temperature of 50-90°C and a drying time of 3-8 hours; more preferably, the drying temperature is 70-80°C and the drying time is 4-6 hours.

[0037] Furthermore, according to a specific embodiment of the present invention, the calcination in step six is ​​carried out under anaerobic conditions, with a calcination temperature of 300–700°C and a calcination time of 2–8 hours; preferably, the calcination temperature is 400–600°C and the calcination time is 3–4 hours.

[0038] Furthermore, according to a specific embodiment of the present invention, the molar ratio of the sulfur-containing compound and ferrous sulfate added is 1.2:1 to 1:1.

[0039] Furthermore, according to a specific embodiment of the present invention, the separation in step six is ​​solid-liquid separation, which can be achieved by any of the existing methods in the art that can achieve solid-liquid two-phase separation, such as filtration or centrifugal separation.

[0040] A third aspect of the present invention provides a catalytic oxidation catalyst obtained by the above preparation method.

[0041] The fourth aspect of the present invention provides a wastewater treatment method in which wastewater enters a reactor and reacts with the above-mentioned catalytic oxidation catalyst and oxidant.

[0042] Furthermore, according to a specific embodiment of the present invention, the wastewater is at least one of chemical wastewater, municipal wastewater, pharmaceutical wastewater, dyeing and printing wastewater, and biochemical effluent, specifically wastewater containing organic pollutants.

[0043] Furthermore, according to a specific embodiment of the present invention, the oxidant is at least one selected from persulfate, percarbonate, hydrogen peroxide, ozone, sodium hypochlorite, ferrate, and permanganate.

[0044] Furthermore, according to a specific embodiment of the present invention, the reaction conditions are room temperature and a volume hourly space velocity (VHSV) of 0.2–3 h⁻¹.-1 The ratio of the amount of oxidant used to the theoretical amount of oxidant required for the raw organic wastewater should not be less than 0.5.

[0045] Compared with the prior art, the catalytic oxidation catalyst and its preparation method provided by the present invention have the following advantages: 1. The catalytic oxidation catalyst provided by this invention has dual active components. Ferrous sulfide not only catalyzes the generation of highly active free radicals from the oxidant but also acts as a co-catalyst, synergistically reacting with transition metal oxides to enhance pollutant removal. The catalyst's application involves a two-stage catalytic reaction: first, oxidant and pollutant molecules react with the outer ferrous sulfide layer, consuming a portion; then, the concentrations of oxidant and organic pollutants that pass through the pores and come into contact with copper oxide are reduced, allowing for further catalytic degradation of pollutants through a deeper catalytic reaction with the more activated copper oxide.

[0046] 2. The catalytic oxidation catalyst provided by this invention has a core-shell structure, with the outer layer being silicon oxide containing ferrous sulfide. During use, copper ions dissolve from the core of the catalyst. However, when these copper ions come into contact with the outer ferrous sulfide layer, a displacement reaction occurs to generate more insoluble copper sulfide and ferrous ions. Both copper sulfide and ferrous ions are excellent catalytic oxidation catalysts and can continue to exert their catalytic effect, thus solving the problem of copper leaching in current copper-based catalysts. This effectively solves the problem of copper ion leaching and avoids secondary pollution; moreover, the in-situ displacement reaction generates new catalysts, improving the long-term effectiveness of the catalyst.

[0047] 3. The applicant's research found that actual industrial wastewater contains not only recalcitrant small-molecule aldehydes and acids, but also a large number of high-molecular-weight compounds. These compounds have long molecular diameters, resulting in high diffusion resistance within catalysts and difficulty in entering the pores. Furthermore, large organic molecules decompose into smaller molecule products during degradation. Therefore, catalysts with a single pore size structure are unlikely to completely treat organic pollutants, thus affecting wastewater treatment efficiency. The catalytic oxidation catalyst provided by this invention uses a microporous material as the inner support, possessing strong adsorption and enrichment capabilities for pollutant molecules. The outer support is mesoporous, serving as both a reaction site for large organic molecules and a channel for reactant molecules, allowing small-molecule pollutants to enter the inner microporous catalytic matrix for reaction. This reduces pollutant diffusion limitations and results in better catalytic performance. This solves the problem of the wide molecular size distribution of organic pollutants in wastewater, making it difficult for catalysts with a single pore size structure to completely treat organic pollutants.

[0048] 4. The catalytic oxidation catalyst preparation method provided by this invention involves layering supports of different pore sizes. The outer support is mesoporous, serving as both a reaction site for large organic molecules and a channel for reacting molecules, allowing small molecule pollutants to enter the inner layer. The inner support has a microporous structure, possessing a strong adsorption and enrichment capacity for pollutant molecules, enriching low-concentration pollutant molecules after reaction in the mesoporous region, thus increasing the reaction driving force. Temperature-sensitive polyvinyl alcohol is also selected to form steric hindrance, protecting the micropores from blockage during the in-situ formation of the mesoporous material and facilitating its removal. This invention organically combines the metal active components during preparation. The copper ions dissolved from the copper oxide supported in the inner layer can react with the in-situ generated nano-ferrous sulfide to generate catalytically active copper sulfide and ferrous ions, solving the problem of copper dissolution in current copper-based catalysts and making the catalyst activity more long-lasting.

[0049] Instruction manual illustrations Appendix Figure 1 This is a pore size distribution diagram of the catalytic oxidation catalyst prepared in Example 1 of the present invention. Detailed Implementation

[0050] The preparation method of the present invention will be further illustrated below with reference to specific embodiments, but the scope of the present invention is not limited to the scope of these embodiments.

[0051] In this paper, the nano-silica alumina clay used consists of nanoparticles of 2–5 nm in size, wherein the sum of the mass of silicon oxide and aluminum oxide accounts for more than 65% of the total mass.

[0052] In this paper, the average degree of polymerization of polyvinyl alcohol used in the polyvinyl alcohol solution was 1750 ± 50.

[0053] In this paper, the ultrasonic conditions were 40 kHz frequency and 150 W power.

[0054] Example 1 70g of granular activated carbon was weighed and impregnated in a copper salt solution at a copper oxide to activated carbon mass ratio of 1:8.8. The copper salt was copper chloride. After drying at 80℃ for 5h, the sample was calcined at 500℃ for 4h in a tube furnace under nitrogen protection to obtain material A. Material A was added to 50mL of a 0.5% (w / w) polyvinyl alcohol solution and ultrasonically vibrated for 1.5h, then dried at 80℃ for 4h to obtain material B. 4g of nano-alumina silica clay, 1.0g of methylcellulose, 2.2g of dodecyltrimethylammonium bromide, 25g of tetraethyl orthosilicate, 100mL of water, and 50mL of ethanol were mixed to obtain material C. Material B was placed in material C and stirred continuously. After reacting at room temperature (25℃) for 3h, rotary evaporation was performed to obtain... The obtained sample was washed with hot water at 80℃, dried at 75℃, and calcined at 500℃ for 3 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved in distilled water to prepare a 0.68 mol / L ferrous sulfate solution. 200 mL of ferrous sulfate solution was added to 0.1 g of sweet potato starch and mixed evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.03 g of Tween 40 was added to a 1.4 mol / L thioacetamide solution and mixed evenly. The mixture was slowly added to material E under nitrogen protection. The pH of the system was adjusted to 7.5, and the reaction was carried out at 75℃ for 1.5 hours. Excess moisture was removed by rotary evaporation at 80℃. The catalyst M-1 was obtained by calcination in a tube furnace at 450℃ under nitrogen protection for 3 hours.

[0055] Example 2 Weigh 65g of granular activated carbon and impregnate it in a copper salt solution at a copper oxide to activated carbon mass ratio of 1:9.3. The copper salt is copper nitrate. Dry at 75℃ for 5 hours, then calcine at 600℃ for 4 hours under nitrogen protection in a tube furnace to obtain material A. Add material A to 55ml of a 0.5% (w / w) polyvinyl alcohol solution, ultrasonically vibrate for 40 minutes, and then dry at 80℃ for 4.5 hours to obtain material B. Mix 5g of nano-alumina silica clay, 1.5g of carboxymethyl cellulose, 3.6g of hexadecyltrimethylammonium bromide, 62g of tetraethyl orthosilicate, 60ml of water, and 40ml of ethanol to obtain material C. Place material B in material C and stir continuously. React at room temperature for 2.5 hours, then evaporate in a water bath at 85℃. Excess moisture was washed with 85℃ hot water, dried at 80℃, and calcined at 550℃ for 4 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved in distilled water to prepare a 0.76mol / L ferrous sulfate solution. 150ml of ferrous sulfate solution was added to 0.1g of methylcellulose and stirred evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.01g of Tween 80 was added to a 0.6mol / L sodium sulfide solution and mixed evenly. The mixture was slowly added to material E under nitrogen protection. The pH of the system was adjusted to 8.0, and the reaction was carried out at 78℃ for 1.2 hours. Excess moisture was removed by rotary evaporation at 75℃. The catalyst M-2 was obtained by calcination in a tube furnace at 500℃ under nitrogen protection for 3 hours.

[0056] Example 3 70g of spherical activated carbon was weighed and impregnated in a copper salt solution (copper sulfate was selected as the copper salt) at a copper oxide to activated carbon mass ratio of 1:14.0. The carbon was dried at 80℃ for 4.5h and calcined at 550℃ for 4h under nitrogen protection in a tube furnace to obtain material A. Material A was added to 66ml of a 0.8% polyvinyl alcohol solution and ultrasonically vibrated for 60min, then dried at 75℃ for 5h to obtain material B. 6g of nano-alumina silica clay, 2.0g of carboxyethyl cellulose, 2.5g of octadecyltrimethylammonium bromide, 43g of tetraethyl orthosilicate, 120ml of water, and 80ml of ethanol were mixed to obtain material C. Material B was placed in material C and stirred continuously. After reacting at room temperature for 5h, rotary evaporation was performed to obtain the sample. The product was washed with 85℃ hot water, dried at 80℃, and calcined at 550℃ for 4 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved in distilled water to prepare a 1.14mol / L ferrous sulfate solution. 80ml of the ferrous sulfate solution was added to 0.1g of hydroxypropyl methylcellulose and stirred evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.04g of Span 40 was added to a 0.6mol / L thioacetamide solution and mixed evenly. The mixture was slowly added to the above system under nitrogen protection. The pH of the system was adjusted to 8.0, and the reaction was carried out at 68℃ for 1.8 hours. Excess moisture was removed by rotary evaporation at 70℃. The product was then calcined in a tube furnace at 500℃ under nitrogen protection for 3 hours to obtain catalytic oxidation catalyst M-3.

[0057] Example 4 Weigh 72g of granular activated carbon and impregnate it in a copper salt solution at a copper oxide to activated carbon mass ratio of 1:24.0. The copper salt is copper acetate. Dry at 70℃ for 5 hours, then calcine at 500℃ for 4 hours under nitrogen protection in a tube furnace to obtain material A. Add material A to 45ml of a 1.0% (w / w) polyvinyl alcohol solution, ultrasonically vibrate for 1.2 hours, and then dry at 70℃ for 6 hours to obtain material B. Mix 3g of nano-aluminosilicate clay, 5.0g of hydroxypropyl methylcellulose, 1.8g of hexadecyltrimethylammonium bromide, 34g of tetraethyl orthosilicate, 90ml of water, and 60ml of ethanol to obtain material C. Place material B in material C and stir continuously. React at room temperature for 3 hours, then perform rotary evaporation. The obtained sample was washed with 80℃ hot water, dried at 75℃, and calcined at 580℃ for 3 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved to prepare a 0.85mol / L ferrous sulfate solution. 200ml of ferrous sulfate solution was added to 0.2g of corn starch and stirred evenly under nitrogen protection. Material D was added to the solution to fully impregnate material E. 0.02g of Span 60 was added to a 2.1mol / L sodium sulfide solution and mixed evenly. The mixture was slowly added to the above system under nitrogen protection. The pH of the system was adjusted to 7.5. The reaction was carried out at 72℃ for 1.3 hours. Excess moisture was removed by rotary evaporation at 80℃. The catalyst M-4 was obtained by calcination in a tube furnace at 450℃ under nitrogen protection for 3 hours.

[0058] Example 5 81g of spherical activated carbon was weighed and impregnated in a copper salt solution (copper nitrate was selected as the copper salt) at a copper oxide to activated carbon mass ratio of 1:20.3. The mixture was dried at 90℃ for 3.5h and calcined in a tube furnace at 550℃ for 4h under nitrogen protection to obtain material A. Material A was added to 60ml of a 1.3% (w / w) polyvinyl alcohol solution and ultrasonically vibrated for 45min, then dried at 80℃ for 5h to obtain material B. 1g of nano-aluminosilicate clay, 3.0g of carboxymethyl cellulose, 2.5g of dodecyltrimethylammonium bromide, 31g of tetraethyl orthosilicate, 150ml of water, and 50ml of ethanol were mixed to obtain material C. Material B was placed in material C and stirred continuously. After reacting at room temperature for 5h, rotary evaporation was performed to obtain... The sample was washed with hot water at 85℃, dried at 80℃, and calcined at 650℃ for 4 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved to prepare a 1.36 mol / L ferrous sulfate solution. 50 ml of the ferrous sulfate solution was added to 0.05 g of carboxymethyl cellulose and stirred evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.01 g of Span 80 was added to a 1.4 mol / L thioacetamide solution and mixed evenly. The mixture was slowly added to the above system under nitrogen protection. The pH of the system was adjusted to 8.0, and the reaction was carried out at 65℃ for 2 hours. Excess moisture was removed by rotary evaporation at 75℃. The catalyst M-5 was obtained by calcination in a tube furnace at 520℃ under nitrogen protection for 3.5 hours.

[0059] Comparative Example 1 100g of spherical activated carbon was weighed, and copper chloride was used as the copper source to impregnate the activated carbon carrier. The loading of copper oxide active component was 7%. The carbon was dried at 85℃ for 8h, and then calcined in a muffle furnace at 550℃ for 6h to obtain material BM-1.

[0060] Comparative Example 2 Weigh 40g of commercially available spherical mesoporous silica support, dissolve ferrous sulfate in oxygen-free water to prepare a 1.14mol / L solution, measure 80ml and add 0.1g of hydroxypropyl methylcellulose, stir evenly under nitrogen protection, add material C to the solution and fully impregnate; add 0.04g of Span 40 to a 0.6mol / L thioacetamide solution and mix evenly, slowly add to the above system under nitrogen protection, adjust the pH of the system to 8.0, react at 68℃ for 1.8h, rotary evaporate, vacuum dry at 85℃ for 6h, and calcine at 500℃ in a tube furnace under nitrogen protection for 3h to obtain catalyst BM-2.

[0061] Comparative Example 3 Repeat Example 1, but without impregnating material A with polyvinyl alcohol solution during the preparation process, to obtain catalyst BM-3.

[0062] Comparative Example 4 Weigh 65g of granular activated carbon and add it to 55ml of 0.5% polyvinyl alcohol solution. Sonicate for 40min, then dry at 80℃ for 3h to obtain material A. Mix 5g of nano-aluminosilicate clay, 1.5g of carboxymethyl cellulose, 3.6g of hexadecyltrimethylammonium bromide, 60g of tetraethyl orthosilicate, 60ml of water, and 40ml of ethanol to obtain material B. Place material A in material B and stir continuously. React at room temperature for 2.5h, then evaporate excess water in an 85℃ water bath. Wash with 85℃ hot water, dry at 80℃, and calcine at 550℃ for 4h under nitrogen protection to obtain material C. Impregnate material C with a copper salt solution at a copper oxide to activated carbon mass ratio of 1:9.3. Select copper salt... Copper nitrate was dried at 75℃ for 5 hours and calcined in a tube furnace at 600℃ for 4 hours under nitrogen protection to obtain material D. Ferrous sulfate was dissolved in distilled water to prepare a 0.76 mol / L ferrous sulfate solution. 150 ml of the ferrous sulfate solution was added to 0.1 g of methylcellulose and stirred evenly under nitrogen protection. Material D was added to the solution and fully impregnated to obtain material E. 0.01 g of Tween 80 was added to a 0.6 mol / L sodium sulfide solution and mixed evenly. The solution was slowly added to material E under nitrogen protection. The pH of the system was adjusted to 8.0, and the reaction was carried out at 78℃ for 1.2 hours. Excess moisture was removed by rotary evaporation at 75℃. The catalyst BM-4 was obtained by calcination in a tube furnace at 500℃ under nitrogen protection for 3 hours.

[0063] Example 6 Take 50cm using a graduated cylinder 3 Catalyst M-1 was placed in an plexiglass reaction tube, and dye wastewater was introduced into the bottom. The reaction conditions were room temperature and a space velocity of 0.25 h⁻¹. -1 The initial TOC was approximately 62 mg / L, and the ozone dosage was 200 mg / L. After stabilization for one day, water samples were taken to test the TOC value of the effluent, and the calculated TOC removal rate was 92%. The copper ion dissolution rate in the effluent was 216 μg / L.

[0064] Example 7 Take 100cm using a graduated cylinder 3 Catalyst M-2 was placed in an plexiglass reaction tube, and dye wastewater was introduced into the bottom. The reaction conditions were room temperature and a space velocity of 0.5 h⁻¹. -1 The initial TOC was approximately 62 mg / L, and the sodium persulfate dosage was 1000 mg / L. After stabilization for one day, water samples were taken to test the TOC value of the effluent, and the calculated TOC removal rate was 70%. The copper ion dissolution rate in the effluent was 188 μg / L.

[0065] Example 8 Take 100cm using a graduated cylinder 3 Catalyst M-3 was placed in an plexiglass reaction tube, with biochemically treated water introduced at the bottom. The reaction conditions were room temperature and a space velocity of 0.5 h⁻¹.-1 The initial TOC was approximately 48 mg / L, the hydrogen peroxide dosage was 300 mg / L, and the wastewater pH was adjusted to 3.2. After stabilizing for one day, water samples were taken to test the TOC value of the effluent, and the calculated TOC removal rate was 83%. The copper ion dissolution rate in the effluent was 329 μg / L.

[0066] Example 9 Take 60cm using a graduated cylinder 3 Catalyst M-4 was placed in an plexiglass reaction tube, with pharmaceutical wastewater flowing through the bottom. Ozone and hydrogen peroxide were simultaneously introduced as oxidants. The reaction conditions were: ambient temperature and a space velocity of 1.0 h⁻¹. -1 The initial TOC was approximately 53 mg / L, the ozone dosage was 200 mg / L, and the hydrogen peroxide dosage was 100 mg / L. After stabilization, water samples were taken to test the TOC value of the effluent, and the calculated TOC removal rate was 88%. The copper ion dissolution rate in the effluent was 53 μg / L.

[0067] Example 10 Take 50cm using a graduated cylinder 3 Catalyst M-5 was placed in an plexiglass reaction tube, with simulated chemical wastewater flowing through the bottom. Sodium persulfate and sodium percarbonate were simultaneously introduced as oxidants. The reaction conditions were: ambient temperature and a space velocity of 2.0 h⁻¹. -1 The initial TOC was approximately 116 mg / L. The wastewater pH was adjusted to 4.5, and the dosage of sodium persulfate was 1000 mg / L and sodium percarbonate was 300 mg / L. After stabilization, water samples were taken to test the TOC value of the effluent, and the calculated TOC removal rate was 68%. The copper ion dissolution rate in the effluent was 68 μg / L.

[0068] Comparative Example 5 Example 6 was repeated, but the catalyst was replaced with BM-1, and the TOC removal rate was 78%. The amount of copper ions dissolved in the effluent was 1275 μg / L.

[0069] Comparative Example 6 Example 7 was repeated, but the catalyst was replaced with BM-3, and the TOC removal rate was 59%. The amount of copper ions dissolved in the effluent was 229 μg / L.

[0070] Comparative Example 7 Example 8 was repeated, but the catalyst was replaced with BM-4, and the TOC removal rate was 72%. The amount of copper ions dissolved in the effluent was 1864 μg / L.

[0071] Comparative Example 8 Example 8 was repeated, but the catalyst was replaced with BM-2, resulting in a TOC removal rate of 69%.

Claims

1. A catalytic oxidation catalyst, wherein the catalyst has a core-shell structure, wherein the core is activated carbon supported on copper oxide and ferrous sulfide, and the outer shell is silicon oxide supported on nano-ferrous sulfide; the catalytic oxidation catalyst comprises two levels of channels, wherein the size of the first level channels is less than 2 nm, and the size of the second level channels is 2–20 nm; the pore volume of the first level channels accounts for 60–90% of the total pore volume, and the pore volume of the second level channels accounts for 10–40% of the total pore volume; the specific surface area of ​​the catalytic oxidation catalyst is 200–1200 m². 2 / g; Based on the weight of the catalytic oxidation catalyst, ferrous sulfide accounts for 5-20% of the catalyst weight, and copper oxide accounts for 2-10% of the catalyst weight.

2. The catalytic oxidation catalyst according to claim 1, wherein, Based on the weight of the catalytic oxidation catalyst, the core weight is 70-90% of the catalyst weight, and the outer shell weight is 10-30% of the catalyst weight.

3. The catalytic oxidation catalyst according to claim 1, wherein, The molar ratio of iron to copper in the catalytic oxidation catalyst is greater than 1.2:

1.

4. A method for preparing the catalytic oxidation catalyst according to any one of claims 1-3, comprising the following steps: Step 1: Mix activated carbon granules with a soluble copper salt solution, and after mixing, dry and calcine under anaerobic conditions to obtain material A; Step 2: Add material A to a polyvinyl alcohol solution for treatment, and then further dry to obtain material B; Step 3: Mix the silicon source, additives, silica-alumina clay, binder, alcohol and water evenly to obtain material C; the additive is at least one of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide; Step 4: Mix material B and material C to react, and then wash, dry and calcine to obtain material D; Step 5: Dissolve ferrous sulfate in deoxygenated water, then add a stabilizer and mix evenly under an inert atmosphere. Then add material D and mix well to obtain material E. The stabilizer is at least one of starch and cellulose. Step 6: Under an inert atmosphere, the sulfur-containing compound, surfactant, and water are mixed evenly and then slowly added to material E. The pH of the system is adjusted to 6-8, and the temperature is raised to 60-80℃ for reaction. After drying and calcination, the catalyst product is obtained.

5. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step one, more than 90% of the activated carbon particles have pores smaller than 2 nm.

6. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The soluble copper salt mentioned in step one is one or more of copper sulfate, copper nitrate, copper chloride, and copper acetate.

7. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The soluble copper salt mentioned in step one is copper nitrate.

8. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step one, the drying temperature is 60–110℃ and the drying time is 2–12 hours.

9. The method for preparing the catalytic oxidation catalyst according to claim 8, wherein, In step one, the drying temperature is 70–90℃ and the drying time is 3–5 hours.

10. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step one, the calcination temperature under anaerobic conditions is 400–800℃, and the calcination time is 2–8 hours.

11. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step one, the calcination temperature under anaerobic conditions is 500–700℃, and the calcination time is 3–4 hours.

12. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step two, the mass concentration of the polyvinyl alcohol solution is 0.1–2.0%.

13. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, Step two involves a mixed process.

14. The method for preparing the catalytic oxidation catalyst according to claim 13, wherein, The mixture is processed under ultrasonic conditions.

15. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step two, the drying temperature is 50–100℃ and the drying time is 3–8 hours.

16. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step two, the drying temperature is 70–80℃ and the drying time is 4–6 hours.

17. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The silicon source in step three is methyl orthosilicate and / or ethyl orthosilicate.

18. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The silicon source in step three is tetraethyl orthosilicate.

19. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The silica-alumina clay in step three consists of nanoparticles with a diameter of 2–5 nm, of which the sum of silicon oxide and aluminum oxide accounts for more than 65% of the total mass of silica-alumina clay.

20. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The alcohol in step three is a small molecule alcohol, which is methanol and / or ethanol.

21. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The binder in step three is at least one of methylcellulose, ethylcellulose, carboxymethylcellulose, and hydroxypropyl methylcellulose.

22. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step four, the drying temperature is 60–110℃ and the drying time is 2–12 hours.

23. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step four, the drying temperature is 70–90℃ and the drying time is 3–5 hours.

24. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step four, the roasting is carried out under anaerobic conditions, with a roasting temperature of 400–800℃ and a roasting time of 2–8 hours.

25. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step four, the roasting is carried out under anaerobic conditions, at a temperature of 500–700℃, for 3–4 hours.

26. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The starch is at least one of sweet potato starch, corn starch, and potato starch; the cellulose is at least one of methylcellulose, ethylcellulose, carboxymethylcellulose, and hydroxypropylmethylcellulose.

27. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The sulfur-containing compound in step six is ​​selected from at least one of sodium sulfide and thioacetamide.

28. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The surfactant in step six is ​​at least one of the Span series surfactants and the Tween series surfactants. The Span series surfactant is at least one of Span 20, Span 40, Span 60, and Span 80; the Tween series surfactant is at least one of Tween 20, Tween 40, Tween 60, and Tween 80.

29. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step six, drying is carried out under anaerobic conditions at a temperature of 50–90°C for 3–8 hours.

30. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step six, drying is carried out under anaerobic conditions at a temperature of 70–80°C for 4–6 hours.

31. The method for preparing the catalytic oxidation catalyst according to claim 29 or 30, wherein, In step six, rotary evaporation drying is used for drying.

32. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step six, the roasting is carried out under anaerobic conditions, with a roasting temperature of 300–700℃ and a roasting time of 2–8 hours.

33. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, In step six, the roasting is carried out under anaerobic conditions, at a temperature of 400–600℃, for 3–4 hours.

34. The method for preparing the catalytic oxidation catalyst according to claim 4, wherein, The molar ratio of sulfur-containing compounds to ferrous sulfate added is 1.2:1 to 1:

1.

35. A wastewater treatment method, wherein wastewater enters a reactor and reacts with a catalytic oxidation catalyst and an oxidant, wherein the catalytic oxidation catalyst is the catalytic oxidation catalyst described in any one of claims 1-3.

36. The wastewater treatment method according to claim 35, wherein, Wastewater is at least one of the following: chemical wastewater, municipal wastewater, pharmaceutical wastewater, dyeing and printing wastewater, and biochemical effluent.

37. The wastewater treatment method according to claim 35, wherein, The oxidant is one of persulfate, percarbonate, hydrogen peroxide, ozone, sodium hypochlorite, ferrate, or permanganate.

Citation Information

Patent Citations

  • Magnetic carbon-supported nanometer ferrous sulfide Fenton-like catalyst and preparation method thereof

    CN110773199A

  • Preparation method and application of modified attapulgite loaded ferrous sulfide

    CN114377647A

  • Preparation method for mesoporous ferrous disulfide / silicon dioxide microsphere composite solid-phase iron source and application of mesoporous ferrous disulfide / silicon dioxide microsphere composite solid-phase iron source

    CN106564964A